Graded epidural anesthesia for open cholecystectomy in elderly patient with ischemic heart disease (Indian Journal of Case Reports, 2021)
Geriatric patients with a limited physiological reserve and associated comorbidities present a challenge to anesthesiologists. Patients with cardiac disease coming for non-cardiac surgical procedures are at increased risk of perioperative cardiovascular events such as myocardial ischemia, myocardial infarction (MI) and are associated with greater morbidity and mortality. In this case report, the patient had a previous history of MI and was a known case of diabetes mellitus with acute cholecystitis with cholelithiasis with anterolateral ischemic heart disease with an ejection fraction of 35%. This patient was posted for open cholecystectomy with CBD exploration and successfully managed under graded epidural anesthesia and had an uneventful recovery.